Childhood Obesity and Academic Performance: The Role of Working Memory - Wu, Nan; Chen, Yulu; Yang, Jinhua; Li, Fei (Frontiers in Psychology, 2017)
The present study examined the role of working memory in the association between childhood obesity and academic performance, and further determined whether memory deficits in obese children are domain-specific to certain tasks or domain-general. A total of 227 primary school students aged 10 to 13 years were analyzed for weight and height, of which 159 children (44 “obese”, 23 “overweight”, and 92 “normal weight”) filled out questionnaires on school performance and socioeconomic status. And then, all subjects finished three kinds of working memory tasks based on the digit memory task in 30 trials, which were image-generated with a series of numbers recall trial sets. After each trial set, subjects were given 5s to recall and write down the numbers which hand appeared in the trial, in the inverse order in which they had appeared. The results showed there were significant academic performance differences among the three groups, with normal-weight children scoring higher than overweight and obese children after Bonferroni correction. A mediation model revealed a partial indirect effect of working memory in the relationship between obesity and academic performance. Although the performance of obese children in basic working memory tests was poorer than that of normal-weight children, they recalled more items than normal-weight children in working memory tasks involving with food/drink. Working memory deficits partially explain the poor academic performance of obese children. Those results indicated the obese children show domain-specific working memory deficits, whereas they recall more items than normal-weight children in working memory tasks associated with food/drink.